Pengaruh Disiplin Belajar Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Sekolah Dasar - Didit Darmawan; Putri Lailatul Maghfiroh; Akhmad Nur Hasyim Romadhoni (Ameena Journal, 2026)
The low quality of basic education in Indonesia remains a problem that affects student learning outcomes. One of the causes is a lack of discipline and motivation to learn, which play an important role in shaping a positive attitude towards learning. Poor learning discipline, such as the habit of procrastinating and arriving late, has an impact on the irregularity of the student learning process. Meanwhile, weak learning motivation causes students to become easily bored, unenthusiastic, and lacking the drive to achieve optimal performance. This study aims to analyse the influence of learning discipline and learning motivation on the learning outcomes of elementary school students. The method used is a literature study with a descriptive qualitative approach, through a review of various relevant previous research results. The results of the study show that learning discipline has a positive effect on shaping students' regularity, responsibility, and perseverance, while learning motivation plays a role in fostering enthusiasm, persistence, and interest in learning among students. The two complement each other in encouraging better learning outcomes. The implications of this study emphasise the important role of teachers and schools in instilling discipline and motivating students through positive behaviour habits, the use of engaging learning methods, and the creation of a conducive learning environment.